NMR-based metabolomics approach to investigate the distribution characteristics of metabolites in Dioscorea opposita Thunb. cv. Tiegun. (15th November 2019) - An, Li; Yuan, Yongliang; Ma, Jingwei; Wang, Hong; Piao, Xiuying; Ma, Junfeng; Zhang, Junfeng; Zhou, Ling; Wu, Xujin
Highlights: A metabolomics study of Dioscorea opposita Thunb. cv. Tiegun exclude-peel and peel. Two different metabolic profiles were compared by NMR-based metabolomics approach. 13 characteristic metabolites responsible for good separation were identified. Distribution of metabolites in Dioscorea opposita Thunb. cv. Tiegun was defined. Abstract: Dioscorea opposita Thunb. cv. Tiegun (DTT), a type of homologous medicinal plant, is commonly used as food in daily life. However, there has always been confusion regarding removal of the peel, as the nutrient metabolite composition of the peel is unclear. Here, a nuclear magnetic resonance (NMR)-based metabolomics approach was used to determine the metabolite distribution in DTT exclude-peel and peel. Thirteen characteristic metabolites with statistical significance were identified and compared using multivariate, univariate and cluster analyses. The results demonstrated that the peel contained the higher levels of α-glucose, batatasin IV, batatasin I, asparagine, β-glucose, protodioscin, threonine, protogracillin, dioscin, and β-sitosteryl acetate, and the samples without the peel had the higher levels of leucine, glutamine and alanine. This study provided scientific data for understanding the distribution characteristics of metabolites in DTT samples, promoting reasonable consumption of DTT.